MODIFICATION OF TUBULAR CERAMIC MEMBRANES BY PYROCARBON FROM CARBONIZED POLYMERS - Goncharuk, Vladislav; Kucheruk, Dmitry; Dubrovina, Liubov; Vyshnevskyi , Oleksii; Dubrovin, Igor; Ogenko, Volodymyr (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2019)
The tubular ceramic membranes of clay minerals were modified with pyrocarbon, which was obtained by carbonizing of polymer precursors at 750 ° С in an argon flow. The precursor to carbonization of membrane II was polyurethane, obtained from laprol and polyisocyanate. A precursor to carbonization of the membrane III was a mixture of polymers formed by the reaction of components of an aqueous solution of a dry solution with NCO-groups of polyisocyanate. As a result of the modification, the membranes became black with a metallic luster. The composition and structure of the membranes were studied by XRF and SEM. The modifier of the membrane II is located in the pore space in the form of sintered agglomerates. The modifier of the membrane III is represented not only by the same agglomerates, but also envelops the structural elements of the membrane material. The apparent density and open porosity for the unmodified membrane are 1.80 g/cm3 and 44.9 %, for membrane II - 1.67 g/cm3 and 39.9 %, for membrane III - 1.68 g/cm3 and 38.3 %. Testing of modified membranes was carried out by water purification from Ca2 + and Fe3 + using the baromembrane method. The concentration of Ca2 + and Fe3 + in aqueous solutions of CaCl2 and FeCl3 was 100 mg/dm3. The period of time until the establishment of dynamic equilibrium in systems during water purification is (1–3 h). After reaching equilibrium the retention factor (R) of Ca2 + during water purification with membrane II is 30% at a pressure of 0.6 MPa, and at a pressure of 1.1 MPa – 18 %. The specific productivity increases with increasing pressure from 10 to 18 dm3/(m2×h). The R of Ca2 + in water purification with membrane III is 22 % at a pressure of 0.4 MPa, and the specific productivity is 47 dm3/(m2×h). The unmodified membrane does not inhibit Ca2 + at all, and its specific productivity at a working pressure of 0.7 MPa decreases from 755 to 500 dm3/(m2×h) in 2-3 hours. The coefficient of retention of Fe3 + by membrane III after 5 hours at a working pressure of 0.4 MPa is 98 % The specific productivity in this case is 8 dm3/(m2×h).